Nanoparticle-mediated specific elimination of soft cancer stem cells by targeting low cell stiffness. (November 2021) - Chen, Xi; Fan, Yadi; Sun, Jinghua; Zhang, Zhipeng; Xin, Ying; Li, Keming; Tang, Kai; Du, Pengyu; Liu, Yiyao; Wang, Guixue; Yang, Mo; Tan, Youhua
Abstract: As the driving force of tumor progression, cancer stem cells (CSCs) hold much lower cellular stiffness than bulk tumor cells across many cancer types. However, it remains unclear whether low cell stiffness can be harnessed in nanoparticle-based therapeutics for CSC targeting. We report that breast CSCs exhibit much lower stiffness but considerably higher uptake of nitrogen-doped graphene quantum dots (N-GQDs) than bulk tumor cells. Softening/stiffening cells enhances/suppresses nanoparticle uptake through activating/inhibiting clathrin- and caveolae-mediated endocytosis, suggesting that low cell stiffness mediates the elevated uptake in soft CSCs that may lead to the specific elimination. Further, soft CSCs enhance drug release, cellular retention, and nuclear accumulation of drug-loaded N-GQDs by reducing intracellular pH and exocytosis. Remarkably, drug-loaded N-GQDs specifically eliminate soft CSCs both in vitro and in vivo, inhibit tumor but not animal growth, and reduce the tumorigenicity of xenograft cells. Our findings unveil a new mechanism by which low cellular stiffness can be harnessed in nanoparticle-based strategies for specific CSC elimination, opening a new paradigm of cancer mechanomedicine. Statement of significance: Low cell stiffness is associated with high malignancy of tumor cells and thus serves as a mechanical hallmark of CSCs. However, it remains unclear whether cellular stiffness can be exploited for specific targeting of soft CSCs. This work reports that soft CSCs exhibit high N-GQD uptake compared to stiff tumor cells, which is regulated by cellular stiffness. Further, soft CSCs have enhanced drug release, cellular retention, and nuclear accumulation of drug-loaded N-GQDs, which enable the specific elimination of malignant CSCs both in vitro and in vivo with minimal side effect. In summary, our study demonstrates that CSC's low stiffness can be harnessed as a mechanical target for specific eradication, which provides a new paradigm of cancer mechanomedicine. Graphical abstract: Image, graphical abstract